2017
DOI: 10.1002/ece3.3113
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gaps for animal seed dispersal: Separating the effects of habitat loss on dispersal distances and seed aggregation

Abstract: Habitat loss can alter animal movements and disrupt animal seed dispersal mutualisms; however, its effects on spatial patterns of seed dispersal are not well understood. To explore the effects of habitat loss on seed dispersal distances and seed dispersion (aggregation), we created a spatially explicit, individual-based model of an animal dispersing seeds (SEADS-Spatially Explicit Animal Dispersal of Seeds) in a theoretical landscape of 0%-90% habitat loss based on three animal traits: movement distance, gut r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 55 publications
(119 reference statements)
0
22
1
Order By: Relevance
“…By contrast, a meta-analysis of a worldwide data set (Fontúrbel et al 2015) suggested that fragmentation reduced interaction rates (visitation or fruit removal), but not disperser diversity (abundance or species richness); at a major biome level, fragmentation reduced disperser diversity only in temperate zones but reduced interaction rates in both temperate and tropical zones. Additionally, inter- or intraspecific variation in disperser traits such as movement distance, movement frequency and gut retention time of seeds represent one mechanism explaining how fragmentation can positively or negatively affect dispersal distances (fragment entrapment, Jones et al 2017).…”
Section: Extrinsic Variation: Ecological Contextmentioning
confidence: 99%
“…By contrast, a meta-analysis of a worldwide data set (Fontúrbel et al 2015) suggested that fragmentation reduced interaction rates (visitation or fruit removal), but not disperser diversity (abundance or species richness); at a major biome level, fragmentation reduced disperser diversity only in temperate zones but reduced interaction rates in both temperate and tropical zones. Additionally, inter- or intraspecific variation in disperser traits such as movement distance, movement frequency and gut retention time of seeds represent one mechanism explaining how fragmentation can positively or negatively affect dispersal distances (fragment entrapment, Jones et al 2017).…”
Section: Extrinsic Variation: Ecological Contextmentioning
confidence: 99%
“…This is most apparent if the absence of the animal disperser leads to dispersal network disruptions (Rogers et al 2017). In a theoretical study, Jones et al (2017) showed that animal traits such as movement distance, activity level and gut retention time interacted with habitat loss such that seed dispersal distances were largest under intermediate habitat loss. Garcia et al (2016) used an isotope-based technique to track bird-mediated seed dispersal and found that small differences in seed and animal traits, for example phenology patterns, could lead to large differences of seed dispersal in response to landscape structure.…”
Section: Rapid Changes In Dispersal In Different Systemsmentioning
confidence: 99%
“…These patterns can be highly consistent over time (Heymann et al., ), increasing the probability of an effect of seed dispersal on SGS. Anthropogenic disturbances that might modify vector behaviour are thus likely to influence seed dispersal patterns and in turn SGS (Jones, Duke‐Sylvester, Leberg, & Johnson, ; McConkey & O'Farrill, ). Our results emphasize the need for future studies on population genetics of animal‐dispersed plants to include ecological and behavioural observations of dispersal vectors as a key for understanding gene flow and spatial distribution of genetic diversity.…”
Section: Future Directionsmentioning
confidence: 99%